Sustainability and Chemistry: Developing Environmentally Conscious Learners (Journal SCIENCEVOLUTION, 2025)
Human well-being has been compromised due to the environmental crisis caused by the overexploitation of natural resources. Within this context, sustainability and green chemistry emerge as a concept aimed at raising awareness about ecological balance, serving as pedagogical strategies for chemistry education. The objective of this bibliographic review was to identify approaches, educational strategies, and their impact on the formation of environmentally conscious students. A qualitative methodology with a narrative design was employed. Twenty-eight academic publications were selected from databases such as Google Scholar, Scielo, Dialnet, ScienceDirect, Elsevier, and ProQuest. It was found that green chemistry is based on 12 principles aimed at reducing the use of non-renewable energies and resources. Furthermore, the importance of updating the curricular plan towards an education with awareness of environmental care is emphasized, utilizing technological tools, but also requiring adequate knowledge for their responsible use. This aims to promote ethical values, critical thinking, and competent skills to act and respond responsibly to the planet's current environmental problems.
Keywords: Sustainability; Chemistry Education; Environmental Education; Environment; Pedagogical Strategies; Green Chemistry